Німецьке землеволодіння на території Катеринославської губернії в другій пол. ХІХ поч. - ХХ ст. - Замуруйцев, А.В. (Культура народов Причерноморья, 2004)
В данной статье рассматриваются проблемы развития немецкого землевладения на юге Украины во второй пол. ХІХ – на ХХ ст.. География исследования охватывает территорию тогдашней Екатеринославской губернии. Особое внимание уделено внутренним причинам, которые обусловили этот процесс. Сделана попытка проследить на конкретных примерах основные тенденции и направления его развития. Важность выбранной темы тесно связана с общей ролью и экономическим влиянием которое оказывало немецкое землевладение на развитие экономики южных районов Украины в то время. The problems of German landownership development on the south of Ukraine at XX centuries are examined in the article. The geography of research covers the territory of the Ekaterinoslavsk province of that time. There has been paired particular attention to the intrinsic causes, witch stipulated this process. There has been made on attempt to trance on specific examples the basic tendencies and directions of its development. The impotence of the topic is closely connected with the general role and economic influence of German agriculture on economic development of Ukraine’s south districts of that time.